Efikasi Diri pada Kepatuhan Minum Obat Anti Tuberkulosis (OAT) - Sutarto Sutarto; Yutricha Salsabila Fauzi; Reni Indriyani; Dyah Wulan Sumekar RW; Anton Wibowo (Politeknik Kesehatan Tanjung Karang, 2019)
Tuberculosis is a chronic disease with a long-time treatment of 6 months or more, self-efficacy in patients is needed routinely to taking medicine which will achieve healing so that it can prevent the transmission of the disease. The patient should have self-efficacy, which is an individual's belief in managing certain behaviors to achieve their healing. Adherence is the level of the patient carrying out treatment methods and behaviors suggested by his doctor or someone else. The purpose of this study was to determine the correlation between self-efficacy to adherence to taking anti-tuberculosis drugs at Panjang Health Center. The study was conducted in September-November 2018 using the Cross-Sectional method. There were 78 respondents in Panjang Health Center following the inclusion and exclusion criteria. Data collection is done by direct interview assisted by a questionnaire guide. The questionnaire used was the Self-Efficacy Questionnaire to assess self-efficacy levels and Morinsky Medication Adherence Scales to assess respondent's medication adherence. The results of the analysis of respondents with 100% effectiveness have a high drug-taking relationship. The conclusion showed a significant correlation between self-efficacy and medication adherence to TBC patients in Panjang Health Center (p-value=0,00).